Effects of silica soil amendment against Exserohilum rostratum, the fungal pathogen of rice brown spot disease in Peninsular Malaysia - Mahmad Toher, Ainu Shahirah; Govender, Nisha; Dorairaj, Deivaseeno; Wong, Mui Yun (Nature Publishing, 2022)
Rice brown spot (BS) exerts devastating agronomic effects on grain quality and overall productivity. In Peninsular Malaysia, BS disease incidence is fairly prevalent and little is known about the diversity of BS pathogens in the local granaries. Fifteen isolates from BS symptomatic rice plants were identified at five different rice granaries across Peninsular Malaysia. Based on the morphological and molecular analyses, two isolates were confirmed as Bipolaris oryzae while the rest were identified as Exserohilum rostratum. Phylogenetic tree analysis revealed that BS incidence in rice granaries in Peninsular Malaysia is caused by a pair of closely related fungal pathogens, E. rostratum and B. oryzae, with the former being more predominant. Cultural characterization of E. rostratum isolate KT831962 showed the best growth and sporulation activity on corn meal agar plates incubated in complete darkness. The effects of calcium silicate (CaSiO3) and rice husk ash (RHA) soil amendment against MR219 and MR253 rice varieties were evaluated during rice-E. rostratum interaction. Results showed that soil amelioration using CaSiO3 and RHA singly and in combination with manganese (Mn) significantly reduced rice BS disease severity. The BS disease index was reduced significantly to less than 31.6% in the silicon-treated rice plants relative to the control plants at 41.2%. Likewise, the grain yield at the harvest stage showed significantly higher yield in the Si-treated rice plants in comparison to the control, non-Si treated rice plants. The findings highlight the potential of RHA agro-waste as Si fertilizer in a sustainable rice production system.